Cladoceras rovumense sp. nov. (Gentianales-Rubiaceae), a new species from southeast Tanzania and northeast Mozambique - Iain Darbyshire; John E. Burrows; Quentin Luke; Clayton Langa (European Journal of Taxonomy, 2022)
Following a review of the circumscription of the genus Cladoceras Bremek. (Rubiaceae) in relation to Tarenna Gaertn., the new species Cladoceras rovumense I.Darbysh., J.E.Burrows & Q.Luke sp. nov. is described from the dry forests of the Rovuma Centre of Plant Endemism (CoE) in southeast Tanzania and northeast Mozambique. This species has previously been known as Tarenna sp. 53, following the revision of African Tarenna by Jérôme Degreef. A comparison to Cladoceras subcapitatum (K.Schum. & K.Krause) Bremek., the only other member of this genus as currently circumscribed, is provided. The new species is assessed as Endangered under the criteria of the IUCN Red List. New records for Mozambique of two further Rovuma CoE endemics are recorded: Celosia patentiloba C.C.Towns. (Amaranthaceae) and Cordia fissistyla Vollesen (Boraginaceae), both of which are globally threatened.